2016
DOI: 10.4317/medoral.21104
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of light based detection systems for early detection of oral cancer and oral potentially malignant disorders: Systematic review

Abstract: BackgroundEarlier detection of oral squamous cell carcinoma (OSCC) and oral potentially malignant disorders (OPMD) is essential for dental professionals to improve patient survival rates. The aim of this systematic review is to to evaluate the effectiveness of devices that utilise the principles of chemiluminescence and tissue autofluorescence as adjuncts in the detection of OSCC and OPMD.Material and MethodsThe electronic retrieval systems and databases searched for relevant articles were PubMed [MEDLINE] and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 28 publications
1
79
0
1
Order By: Relevance
“…16,18,27,[32][33][34][35] A handheld device, the VELscope, was proposed for clinicians to noninvasively direct the fluorescence images of oral cavity tissues. 16,33,35,[37][38][39][40][41][42][43][44][45][46][47] Some studies observed the spectra of autofluorescence on different anatomical sites and found some characteristics between different sites. The results indicated that quantitative autofluorescence imaging can provide a noninvasive and objective method for detecting oral neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…16,18,27,[32][33][34][35] A handheld device, the VELscope, was proposed for clinicians to noninvasively direct the fluorescence images of oral cavity tissues. 16,33,35,[37][38][39][40][41][42][43][44][45][46][47] Some studies observed the spectra of autofluorescence on different anatomical sites and found some characteristics between different sites. The results indicated that quantitative autofluorescence imaging can provide a noninvasive and objective method for detecting oral neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…We present example RCM images and video-mosaics, obtained in healthy volunteer subjects and patients from both clinical and surgical settings (Figs. [3][4][5][6][7][8][9]). The feasibility of video-mosaicking is demonstrated at two key clinically relevant depths.…”
Section: Resultsmentioning
confidence: 99%
“…Figures [3][4][5][6][7] show example cases of RCM imaging and video-mosaicking in normal mucosa on volunteers in the clinical setting. In the epithelium and at the epithelial junction, we observe honeycomb pattern of cells with cobblestone pattern of nuclei.…”
Section: Normal Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Currently the group is currently finalizing data from a multicenter, phase 3 trial to validate their results [28] . While the laboratory results of examining tissue autofluorescence have shown significant promise in the discrimination of malignant tissues, actual application in clinical trials has been extremely variable in terms of specificity [29,72] .…”
Section: Tissue Auto Fluorescencementioning
confidence: 99%